Gendered Dynamics in Jail Reformation: Work Insights of Women Officers in Jail Facilities - Barbarona, Charo Lyn; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the work insights, coping experiences, and personal and professional aspirations of women jail officers assigned to the Carmen, Talibon, and Ubay District Jails in Bohol, Philippines. It was anchored on Self-Efficacy Theory, Competence Motivation Theory, and Protection Motivation Theory. A qualitative transcendental phenomenological design was employed involving ten women jail officers with at least three years of service, selected through purposive convenience sampling. Four informants participated in individual in-depth interviews, while six participated in a focus group discussion. Data were gathered using a validated and pre-tested open-ended interview guide, research journal, and audio or video recording devices. The responses were transcribed, translated, coded, and analyzed using Colaizzi’s phenomenological analysis procedure, with member checking conducted to confirm the interpretations. Eight emergent themes were identified. Under the work insights of the informants in the performance of their duties, the positive experiences were Meaningful Employment and Recognition and Supportive Work Relationships and Growth, while the negative experiences were Emotional Disconnection and Isolation and Operational Challenges and Moral Frustrations. Coping with problems encountered in the performance of their duties was reflected in Building Resilience through Camaraderie and Initiative and Institutional and Psychological Support System. Their desires to improve their personal and professional growth were reflected in Ambition for Growth and Positive Change and Vision for a Purposeful Future. The study concludes that women jail officers remain committed and resilient despite occupational, emotional, and institutional challenges. It recommends stronger psychological support, recognition programs, professional-development opportunities, open communication, gender-responsive policies, and improved organizational assistance. The study supports SDG 3, SDG 5, SDG 8, and SDG 16 by promoting occupational well-being, gender equality, decent work, and inclusive correctional institutions. Its sustainability impact lies in strengthening institutional capacity, employee welfare, gender-responsive governance, and humane jail management.